Studies in leaf domatia-mite mutualism in South Africa - Situngu, Sivuyisiwe (Rhodes University, Faculty of Science, Botany Department, 2018)
Plants have various traits which allow them to cope and resist their enemies including both insects and fungi . In some cases such traits allow plants to build mutualistic relationships with natural enemies of plant pests. This is the case in many dicotyledonous plants which produce leaf domatia. Leaf domatia are plant cavities usually found in the axils of major veins in the abaxial side of leaves. They are usually associated with mites and often mediate mutualistic relationships with predacious mites. Mites use leaf domatia primarily for shelter, to reproduce, and to develop. In turn, plants benefit from having predaceous mites on their leaves, because mites act as plant "bodyguards" and offer defence against pathogens and small arthropod herbivores. This phenomenon has been well documented all over the world, but Africa remains disproportionally understudied. The aim of this study was to fill the gap that exists in our knowledge of the extent of the distribution of leaf domatia-mite mutualisms and generate a better understanding of the diversity of mites found within leaf domatia from an African perspective. This was done by surveying plant species that bear leaf domatia from different vegetation types in South Africa. The plants with leaf domatia were examined for the presence of mites in order to determine patterns of mite abundance and diversity and, in so doing, address the following questions: "¢ Does each tree species host have a specific mite or mite assemblage? "¢ Do some mites prefer certain types of leaf domatia? "¢ Do mites prefer a specific place in the tree canopy and does the microclimate in the tree canopy affect the distribution of mites? "¢ Do different vegetation sites and types differ in their mite diversity and species composition? "¢ Does mite abundance and diversity vary with seasons? Do coffee plantations have a different suite of mites than the adjacent forest? The anatomical structures of leaf domatia from six selected plant species(Coffea arabica, Gardenia thunbergia, Rothmannia capensis, Rothmannia globosa (Rubiaceae), Ocotea bullata (Lauraceae) and Tecoma capensis (Bignoniaceae) with different types of leaf domatia were also studied. The results from this study suggested that the key futures which distinguish domatia are the presence of an extra layer of tissue in the lower epidermis, a thick cuticle, cuticular folds, the presence of trichomes and an invagination. This study provides a better understating of the structure of leaf domatia. Leaf domatia bearing plants are widely distributed in South Africa, and species and vegetation-specific associations were assessed. Over 250 plant specimens with leaf domatia were collected and examined and more than 60 different mite species were found in association with the sampled plant species. The majority of mites found within the domatia of these tree species were predaceous and included mites from Stigmatidae, Tydeidae and Phytoseiidae. Furthermore, 15 new species were collected, suggesting that mites are understudied in South Africa. This study showed that the different vegetation types sampled did not differ markedly in terms of their mite biota and that similar mites were found across the region, and the association between leaf domatia and mites was found to be opportunistic and that mites had no preference for any particular domatia types. No host specificity relationship was observed between plants and mites. The assessment of mites associated with Coffea arabica showed that indigenous mites are able to colonise and establish a beneficial mutualism on exotic species. This is important as it ascertains that economically important plants that are cultivated outside their area of natural distribution can still benefit from this mutualism. This study also found that mite abundance and diversity in plants with leaf domatia were influenced by factors such as temperature, relative humidity and rainfall. Mite communities found in association with domatia changed as the year progressed and over the seasons. The seasonal fluctuations varied between the sampled plant species. In addition, this study found that mites were sensitive to extreme environmental conditions, and thus, mites preferred leaves found in the lower parts of the tree canopy and avoided exposed leaves. This study provides a better understanding of the distribution of domatia bearing plants in South Africa and their associated mites and contributes to our knowledge of the biodiversity of mites in the region. Furthermore, this study also adds to our understanding of the leaf domatia - mite mutualism in Africa. The applied example looking at the plant-mite mutualism in Coffea arabica highlights the importance of this mutualism in commercial plants.
Keywords: Insect-plant relationships; Mites; Mutualism (Biology); Biological pest control agents